2003
DOI: 10.1074/jbc.m307933200
|View full text |Cite
|
Sign up to set email alerts
|

The PIM-2 Kinase Phosphorylates BAD on Serine 112 and Reverses BAD-induced Cell Death

Abstract: Hematopoietic growth factors mediate the survival and proliferation of blood-forming cells, but the mechanisms through which these proteins produce their effects are incompletely known. Recent studies have identified the pim family of kinases as mediators of cytokinedependent survival signals. Several studies have identified substrates for the pim-1 kinase, but little is known about the other family members, pim-2 and pim-3. We have investigated potential functions for the pim-2 kinase in factor-dependent muri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
220
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(241 citation statements)
references
References 28 publications
7
220
0
5
Order By: Relevance
“…In the past, Pim-1 has been shown to have multiple protective effects at the mitochondria (15,26,27), but a relationship between Pim-1 and mitochondrial morphologic dynamics has not been examined previously. Pim-1 overexpression prevented Drp1 accumulation at mitochondria and decreased total Drp1 levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, Pim-1 has been shown to have multiple protective effects at the mitochondria (15,26,27), but a relationship between Pim-1 and mitochondrial morphologic dynamics has not been examined previously. Pim-1 overexpression prevented Drp1 accumulation at mitochondria and decreased total Drp1 levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were collected, washed in PBS, and lysed in 1% Triton lysis buffer (Yan et al, 2003). Samples were denatured at 1001C for 5 min.…”
Section: Western Blottingmentioning
confidence: 99%
“…Previously, we and others have shown that Flt3-dependent survival signals are primarily mediated by activation of the PI3K-AKT pathway. 8,31 Indeed, both Pim2 and Akt are known to phosphorylate the antiapoptotic protein BAD, 15,16 suggesting that both pathways impinge on apoptosis regulation through modification of the Bcl2 family of proteins. Overexpression of Pim2 did not enhance the activity of AKT in our experiments (data not shown), as has been described previously.…”
Section: Pim2 In Leukemic Transformation S Agrawal Et Almentioning
confidence: 99%
“…6,11,12 Pim1 and Pim2 are shown to protect hematopoietic cells from cell death, and deficiency of Pim kinases leads to reduced body size in knockout mouse studies. 10,[13][14][15][16][17] Interestingly, when primary bone marrow-derived blast cells from patients with AML were assessed for Pim2 expression using quantitative RT-PCR, many AML patients showed overexpression of Pim2 regardless of the presence of Flt3-ITD mutations. 2 This suggests that Pim2 expression may be increased by mechanisms other than Flt3-ITD and points to a role for Pim2 in the pathogenesis of AML.…”
Section: Introductionmentioning
confidence: 99%